The study of gill disease of cultured Atlantic salmon (Salmo salar. L) in Ireland with an emphasis on the role of epitheliocystis as a causative agent : descriptive pathology, aetiology and epidemiology - Mitchell, Susie (Trinity College (Dublin, Ireland). Department of Zoology, 2011)
Gill disorders have emerged as one of the most important health issues in the farming of Atlantic salmon (Salmo salar) in Ireland in recent years. The aetiology of these conditions is frequently multifactorial. Environmental challenges such as harmful algal blooms and zooplankton swarms can be involved, in addition to a range of infectious agents. The importance of some of these agents in terms of fish health remains to be elucidated.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin.